Analysis of the Translation of the Kazakh Non-Equivalent Vocabulary (Based on I. Yessenberlin’s Trilogy “Nomads”) - Mukhtarova С.С. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2018)
The article deals with the translation problems of Kazakh non-equivalent vocabulary from I. Yessenberlin’s novel “Nomads”. Non-equivalent vocabulary reflects the peculiarity of the national culture of the ethnos, preserves the national and cultural significance, thus transferring the identity of the national culture from one generation to another and presenting a great difficulty for translators. The aim of the research is to define the translation ways of linguocultural features of Kazakh non-equivalent vocabulary into Russian and English. There has been used the continuous sampling method, comparativetypological, descriptive, systemization methods and componential analysis. During the research it has been defined that the translators have used all the translation methods in the translation of Kazakh nonequivalent vocabulary. We consider as the most adequate method of translation the use of the combined method (transliteration and descriptive), because only this translation method gives the reader a chance to indulge in the text and thus saves the national colouring of the vocabulary